2015
DOI: 10.1371/journal.pone.0143337
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity and Dispersal Patterns of Protected Biogenic Reefs: Implications for the Conservation of Modiolus modiolus (L.) in the Irish Sea

Abstract: Biogenic reefs created by Modiolus modiolus (Linnaeus, 1758) (horse mussel reefs) are marine habitats which support high levels of species biodiversity and provide valuable ecosystem services. Currently, M. modiolus reefs are listed as a threatened and/or declining species and habitat in all OSPAR regions and thus are highlighted as a conservation priority under the EU Marine Strategy Framework Directive (MSFD). Determining patterns of larval dispersal and genetic connectivity of remaining horse mussel populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…As such, establishing reasonable baselines to inform adaptive management of restoration efforts where O. edulis habitats are currently absent is a key priority. On a larger scale, baselines regarding the current and historical extent of O. edulis reefs provide critical background for determining eligible sites for oyster restoration, which should be used in combination with habitat suitability (Shelmerdine & Leslie, 2009) and site connectivity mapping (Gormley et al, 2015) to ensure that restoration sites across Europe are optimally co‐located. Finally, understanding the current and historical extent of oyster reefs in Europe is also important for communication and outreach (Fitzsimons et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…As such, establishing reasonable baselines to inform adaptive management of restoration efforts where O. edulis habitats are currently absent is a key priority. On a larger scale, baselines regarding the current and historical extent of O. edulis reefs provide critical background for determining eligible sites for oyster restoration, which should be used in combination with habitat suitability (Shelmerdine & Leslie, 2009) and site connectivity mapping (Gormley et al, 2015) to ensure that restoration sites across Europe are optimally co‐located. Finally, understanding the current and historical extent of oyster reefs in Europe is also important for communication and outreach (Fitzsimons et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Such genetic homogeneity is readily consistent with results from other studies. Biophysical modelling of larval dispersal for a number of species has predicted that the hydrography of the region would facilitate larval dispersal between Irish and British coasts (Coscia et al, 2013;Gormley et al, 2015). In a study employing near identical sample collection sites to this one, Watson et al (2016) found no genetic structure across the Irish and Celtic Sea in the European lobster (Homarus gammarus), a species for which dispersal is restricted to the larval stage unlike crab where postlarval dispersal is reported.…”
Section: Discussionmentioning
confidence: 99%
“…Such genetic homogeneity is readily consistent with results from other studies. Biophysical modelling of larval dispersal for a number of species has predicted that the hydrography of the region would facilitate larval dispersal between Irish and British coasts (Coscia et al ., 2013; Gormley et al ., 2015). In a study employing near identical sample collection sites to this one, Watson et al .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the increased abundance of juveniles at North Lleyn and Port Appin (Figure 3) may be due to the higher current flows observed (Comely, 1978; Brown, 1984). Such conditions may lead to increased connectivity via improved larval supply from other reefs in the Irish Sea (Anwar et al , 1990; Rees et al , 2008; Gormley et al ., 2015b) and Loch Linnhe respectively (Rees, 2009; Moore et al ., 2012). Conversely, the decreased abundance of juveniles in Scapa Flow may be caused by limited connectivity, due to reduced tidal flow and a lack of known neighbouring reefs (Rees, 2009; Gormley et al ., 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…Results here provide baseline values against which changes in such factors may be monitored thereby aiding detection of potential climate change impacts. Further, where populations are genetically connected (Gormley et al ., 2015a, b) and thus may have similar adaptive capacity, consideration of the effects of temperature in more southern regions may give some indication of effects to be expected in more northerly populations. However, given both the longevity of M. modiolus and current acceleration in rates of climate change, many reefs will have limited opportunity for adaptation.…”
Section: Discussionmentioning
confidence: 99%